Enhancing Scientific Communication Skills of Pre-Service Science Teacher Through Guided Inquiry Learning on Basic Physics Laboratory Activities - Abidin Pasaribu; Evelina Astra Patriot; Ahmad Fitra Ritonga; Saparini Saparini; Melly Ariska; Azizah Putri Berimah (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to describe the enhancement of students' science communication skills through the application of guided inquiry learning models in laboratory activities. The method used to describe science communication skills is to use pre-experiment research. The samples used in this study were 60 physics education students in the odd semester 2023/2024 who took basic physics practicum courses. The implementation of the guided inquiry learning model in the four meetings. The results of improving science communication skills were based on three indicators that researchers have limited. The result analysis used non-test instruments like observation sheets. The sub-scientific communication skills are: 1) searching information, 2) scientific writing, and 3) representing information. Based on the observation results, it was found that the application of the guided inquiry learning model can train students' science communication skills in sub-skills of seeking information with a percentage increase of 74%, sub-skills of scientific writing with a rise of 67% and sub-skills of representing information at an increase in percentage of 76%. Each average score on the third and fourth meetings shows that science communication skills are in the very skilled category